ОЦЕНКА ТЕРАПЕВТИЧЕСКОЙ ЭФФЕКТИВНОСТИ ВАРФАРИНА ПРОИЗВОДСТВА ЗАО «КАНОНФАРМА ПРАДАКШЕН» (РОССИЯ) - М. В. Хруслов; Е. В. Ройтман (SINAPS LLC, 2014)
Warfarin by «Kanonpharma production» (Russia) and original Warfarin have the similar safety and tolerability. We need some increase of dose of Warfarin by «Kanonpharma production» to reach target rate of INR, then in case of original Warfarin usage. But for 1.5 month of treatment this characteristic doesn't mention to reach target INR. Considering that Warfarin by ZAO «Kanonpharma production» is less expensive then original, they are comparable for ratio «price/effect».